Assessment of Function of Eustachian Tube in Oral Submucous Fibrosis – A Tympanometric Study - Chandran, Alagiri (J Clin Diagn Res, 2016)
INTRODUCTION: Oral Submucous fibrosis (OSMF) is a chronic insidious disease of oral mucosa that occurs due to areca-nut chewing, consumption of chillies, autoimmunity and genetic predisposition. The disease starts with burning sensation and inability to tolerate spicy foods with gradual reduction in mouth opening due to fibrosis of the oral mucosa. The extension of fibrosis into the naso pharynx leads to reduction in hearing efficiency. It is a potentially malignant lesion and can transform into oral cancer. AIM: To assess the functional impairment of eustachian tube by audiogram and tympanometry in both ears in stage IV and stage III OSMF cases. MATERIALS AND METHODS: This was a case-control study in which 30 cases of OSMF, which included 15 stage IV (30 ears), 15 stage III (30 ears) were compared with 15 normal controls. RESULTS: 1) Stage IV cases showed 76.3% positive audiogram with 63.3% of cases having Sclerosis of tympanic membrane i.e. As curve in Tympanogram; 2) 43.3% of Stage III cases showed positive audiogram with 46.7% of cases having Sclerosis of tympanic membrane i.e. As curve in tympanogram; 3) 100% negative audiogram with 100% normal A curve was seen in all controls. CONCLUSION: From this study, it is evident that functions of Eustachian tube were affected as fibrosis of oral mucosa progressed.